Management of Educational Facilities and Infrastructure - Anilamsari, Hernika Dwi; Benty, Djum Djum Noor (Universitas Negeri Malang, 2024)
The management of facilities and infrastructure in schools is an important aspect in creating a conducive learning environment. This article aims to analyze the process of facilities and infrastructure management which includes planning, procurement, distribution, maintenance, inventory, and elimination of educational facilities. This study uses a literature study method by collecting data from various literature sources. The results showed that regular planning and support from the government and the school contributed positively, but there were obstacles such as limited management authority and lack of awareness of the facilities. Therefore, there needs to be collaboration between all parties and increased awareness to maximize the use of facilities and infrastructure, in order to achieve effective and efficient educational goals.